Evaluación de la vitamina C en la recuperación de pacientes caninos sometidos a cirugía (OVH) - Lema Castillo, Cinthia Estefania (2016)
The present research was conducted in San Miguel de Bolívar city, it had as theme "Evaluation of C vitamin in the recovery of canine patients undergoing surgery (ovh)"whose objetives werw to determine the influence of C vitamin in the surgical wound healing, decrease the time of healing of wounds in patients undergoing surgery; and value the recovery of canines during the postoperative period, we worked with 40 female canines five races, of different ages with different weights, Cvitamin was used in doses of 80 mg/kg 24 hours before surgery administering intravenously, the time of surgery was 25 minutes on average, with a size of 4cm wound, with a time of 30 minutes post-anesthetic recovery. the time of wound healing was 2 to 5 days in what refers to the degree of analgesia was assessed according to the table tab of the pain scale 4 avet modified in which was found in the range of 1 to 4 as it is indicating that patients had low postoperative pain, protein values and hematocrists of all patients were with in the reference values.